Conservation planning for river-wetland mosaics: A flexible spatial approach to integrate floodplain and upstream catchment connectivity. (August 2019) - Reis, Vanessa; Hermoso, Virgilio; Hamilton, Stephen K.; Bunn, Stuart E.; Linke, Simon
Abstract: Systematic conservation planning has contributed to the spatial design of reserve networks in river ecosystems by recognizing the importance of maintaining longitudinal connectivity. In the complex and dynamic landscapes of river-floodplain systems, however, it is still challenging to account for the longitudinal and, especially, lateral connections that are relevant to their management. Adequate protection of floodplain ecosystems requires accounting for spatio-temporal connectivity among all waterbodies that compose the riverine landscape. In this study we present a new framework to account for both within-floodplain (lateral) and longitudinal river connectivity in freshwater systematic conservation planning. We run four prioritization scenarios comparing different rules of connectivity for the rivers and floodplains of the entire Amazon River basin. The scenarios involved the comparison of local protection only versus integrated upstream protection for floodplains. The spatial framework combined two types of planning units, with connectivity between them assessed using two distance-based measures for within-floodplain and upstream-downstream connectivity. We found different levels of protection afforded to floodplain wetlands across scenarios. The scenario including only within-floodplain connectivity failed to detect the propagation of impacts from the surroundings and upstream catchment. In contrast, the scenario that integrated within-floodplain and longitudinal river connectivity agglomerated subcatchments around the priority wetlands, generating catchment-integrated units that efficiently reduced impacts. We also demonstrate that the integrated connectivity can be manipulated to meet different conservation objectives. The new approach presented here offers more ecologically meaningful protection to floodplains because it considers local wetland boundaries and connectivity within wetland complexes together with connectivity with the upstream landscape. This framework can be applied to integrated wetland conservation and management throughout the world and provide a valuable tool to safeguard the ecosystem functioning of complex river-floodplain mosaics.